Access to Justice in English Project : Access to Quebec government websites in English : Executive Summary and Recommendations - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English project (“the Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec.

Projet Accès à la justice en anglais : Accès aux sites Web du gouvernement du Québec en anglais : Rapport exécutif et recommandations - Quebec Community Groups Network (QCGN) (2023)
Le projet Accès à la justice en anglais du QCGN (« le Projet ») repère et recherche les domaines où la communauté d’expression anglaise éprouve des difficultés à accéder à ses droits en mettant l'accent sur l'accès des communautés aux services publics. Il utilise l'information comme une ressource stratégique pour comprendre et améliorer l'accès à la justice en anglais au Québec.

Press Release : Making Homemade Tomato Sauce with Greg on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Organic Gardening with Hannah on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Tango Dancing with Mireille & Friends on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Making Jam with Susan on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : The Flamboyant World of Drag with Barbada on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Community Organization of Lanaudière (ECOL) (2021)

Press Release : Wine Pairing with Ana on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Horse Therapy with Karine on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Indigenous Hoop Dancing with Makhena on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Animal Fostering with Cindy on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Spring Special! Gardening in Small Spaces on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Flower Arranging on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Laughter Yoga on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : New Episode of Web Series for Seniors We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : New York Times Bestselling Author Louise Penny Is The Guest of the Web Series for Seniors We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Celebrated New York Times Bestselling Author Louise Penny, on Senior’s Web Series We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : A Holiday Concert of Quebec Performers at Martha Wainwright's URSA Follows Incredibly Popular First Episode of "We're All In This Together" - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2020)

Press Release : Launch of Project We Are All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2020)

Study on the Use of the Internet, New Media and Social Media and Respect for Canadians' Language Rights : A Study on Air Canada's Obligations Under the Offiicial Languages Act - Quebec Community Groups Network (QCGN) (2011)